2022
DOI: 10.1159/000525281
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibition and Beyond in BRCA-Associated Breast Cancer in Women: A State-Of-The-Art Summary of Preclinical Research on Risk Reduction and Clinical Benefits

Abstract: In mammalian cells, DNA damage response initiates repair by error-free homologous recombination (HRR) or by error-prone non-homogeneous end joining (NHEJ). DNA damage is detected by PARP proteins that facilitate this repair, both in normal cells and in cancer cells. Cells that contain BRCA1/2 mutations have an HRR deficient repair mechanism which may result in unrepaired one-ended double-strand breaks and stalled replication forks, considered as the most lethal cell damage. Here we review the state of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Family et al (2014) analyzed single-nucleotide polymorphisms (SNPs) in DNA bypass polymerase genes, such as DNA polymerase theta (POLQ), and their association with BC and BC subtypes in AAW and White women, concluding that the analyzed SNPs are in high linkage disequilibrium in both races, but these can be associated with the risk of luminal BC [54]. Cells with BRCA1/2 mutations have a homologous recombination (HRR)-deficient repair mechanism, so the poly(ADP-ribose) polymerase (PARP) inhibitors can be considered a precision-targeted anticancer drug in BRCA1/2-mutated women [55]. Hsiao and Lu (2021) showed that the identification of accessible homologous recombination deficiency (HRD)-type genes, which are relevant based on race, has significant clinical relevance for various malignancies, including BC [56].…”
Section: Genetics/genomics Of Breast Cancer Disparitiesmentioning
confidence: 99%
“…Family et al (2014) analyzed single-nucleotide polymorphisms (SNPs) in DNA bypass polymerase genes, such as DNA polymerase theta (POLQ), and their association with BC and BC subtypes in AAW and White women, concluding that the analyzed SNPs are in high linkage disequilibrium in both races, but these can be associated with the risk of luminal BC [54]. Cells with BRCA1/2 mutations have a homologous recombination (HRR)-deficient repair mechanism, so the poly(ADP-ribose) polymerase (PARP) inhibitors can be considered a precision-targeted anticancer drug in BRCA1/2-mutated women [55]. Hsiao and Lu (2021) showed that the identification of accessible homologous recombination deficiency (HRD)-type genes, which are relevant based on race, has significant clinical relevance for various malignancies, including BC [56].…”
Section: Genetics/genomics Of Breast Cancer Disparitiesmentioning
confidence: 99%
“…Additionally, inhibitors targeting other DNA repair pathways, such as ATR and CHK1, are under investigation in clinical trials for TNBC ( 63 ) ( Table 2 ). PARP inhibitors represent a significant advancement in the treatment of breast cancer, particularly in patients with TNBC who harbor BRCA1/2 mutations ( 64 ). By exploiting the defective DNA repair mechanisms in BRCA-mutated Tumors, PARP inhibitors disrupt DNA damage repair pathways, leading to synthetic lethality and ultimately Tumor cell death ( 65 ).…”
Section: Therapeutic Strategies For Tnbcmentioning
confidence: 99%
“…HRR utilizes the sister chromatid as a template, whereas NHEJ promptly seals DNA ends, potentially introducing sequence modifications. Together, these mechanisms ensure chromosome stability [ 10 ]. Tumors bearing BRCA mutations exhibit HRR deficiency due to a dual effect: a hereditary mutation in one allele and the inactivation of the other through loss of heterozygosity.…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, the treatment of TNBC patients with PARP inhibitors in combination with platinum-based chemotherapy, either before or after, has demonstrated beneficial outcomes in the OlympiAD and EMBRACA open-label randomized phase three trials, utilizing olaparib and talazoparib, respectively. This finding is particularly significant given that approximately two-thirds of triple-negative patients possess proficient BRCA1 and lack homologous recombination deficiency [ 10 , 11 , 12 ]. Extensive research into combining PARP inhibitors for metastatic BC, particularly veliparib, reveals promising synergy with cytotoxic agents, enhancing effects even in tumors that are unresponsive.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation